Comparative study of corrosion behaviour of galvanized steel and coated Al 3103 roofing sheets in carbonate and chloride environments (2009)
This work studied the comparative corrosion behaviour of Al3101 and galvanized steel roofing sheets in 1M, 0.5M and 0.3M solutions of sodium carbonate and sodium chloride. Samples of the aluminium and galvanized sheets were subjected to the different environments for thirthy days. The electrode potentials, in mV(SCE), were measured everyday. Electrode potential measuremets were taken everyday for thirty consecutive days. Weight loss or gain measurements were taken every three days for the duration of the exposure period. The results showed sodium chloride environment had higher corrosive effects on the galvanized roofing sheet than sodium carbonate environment while the reverse was true for aluminium sheets. Also, galvanized steel roofing corroded more than aluminium roofing in both carbonate and chloride environments. Corrosion of galvanized steel roofing was continous throughout the exposure period in all the environment used. Galvanized steel roofing sheet is not good material for roofing in carbonated and chloride environments or in industrial environments where chloride or carbonate contamination is possible.